Isolation and identification of bacteria associated with spoilt tomato (Lycopersicon esculentum) sold at Gombe main market, Gombe State - Hafsat, J.; Gurama, A.; Mansur, A (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
Tomato (Lycopersicon esculentum) contains high water content making it prone microbial spoilage, thus causing a significant public health concern. This study is aimed at determining the various pathogenic bacteria associated with spoiled tomatoes sold in Gombe Main Market, Gombe State. A total of 50 spoilt tomatoes samples sold in Gombe Main Market were collected for analysis. Collected samples were cultured on Nutrient agar, Eosin Methylene Blue agar, Manitol Salt agar, Samonella Shigella agar, and Mueller Hinton agar. Five species of bacteria were isolated and identified based on their morphological and biochemical characteristics. The bacterial species isolated include: Bacillus spp, Escherichia coli, Klebsiella aerogenes, Shigella and Staphyloccocus aureus. The antibiogram of bacterial isolates was determined by Kirby- Bauer disk-diffusion method. Varying levels of antibiotic sensitivities and resistances were observed on all the bacteria isolated. The bacteria especially gram negative, were found to be key responsible for tomato spoilage. The presence of antibiotic resistant bacteria amongst tomatoes raises concern on public health risks. Technological improvement of harvesting, packaging, handling, storage and preservation could reduce tomato fruit losses and invariably enhance shelf life and quality.